Statistical multisource-multitarget information fusion - Mahler, Ronald P. S (Artech House information warfare library, 2014)
This book addresses the large number of significant advances that have appeared since the publication of the first book, both practical and theoretical. The book presents systematic integral and differential calculus for multisource-multi